Risk of preeclampsia by gestational weight gain in women with varied prepregnancy BMI: A retrospective cohort study - Gong, Xiaoli; Li, Jiaxin; Jiang, Yuanhui; Yuan, Pengbo; Chen, Lian; Yang, Yike; Li, You; Sun, Mengxing; Zhao, Yangyu; Shi, Huifeng; Wei, Yuan (Frontiers in Endocrinology, 2022)
Introduction: Despite the important clinical significance, limited data on the joint contribution of prepregnancy body mass index (BMI) and gestational weight gain (GWG) to preeclampsia, the second leading cause of maternal mortality worldwide. This study aimed to estimate the risk of preeclampsia by GWG among women with varied prepregnancy BMI. Methods: We conducted a retrospective cohort study using data of 117 738 singleton pregnant women aged 18–49 years from 150 maternity hospitals in China between 2015 and 2018. GWG was calculated as the measured weight at the time of preeclampsia assessment minus prepregnancy weight; GWG velocity was calculated as the GWG divided by the gestational age at weighing. The non-linear associations of GWG with preeclampsia were examined by restricted cubic spline regression analysis according to prepregnancy BMI. The association of the GWG categories with preeclampsia was further examined by performing robust Poisson regression stratified by the prepregnancy BMI categories. Results: Among participants, 2426 (2.06%) were diagnosed with preeclampsia. Compared to women with normal BMI, those who were overweight and obese had 1.92- fold (95%CI, 1.73–2.14) and 5.06- fold (95%CI, 4.43–5.78) increased risks for preeclampsia, respectively. The association of GWG velocity with preeclampsia was presented as a J-shaped curve with the varied inflexion point (where the rate of preeclampsia was 2%), which was 0.54, 0.38, and 0.25 kg/week in women with normal BMI, overweight, and obesity, respectively; a steep risk rise was observed along with GWG velocity beyond the inflexion points. The overall adjusted relative risk for preeclampsia was calculated among women with the different GWG categories of GWG. Conclusions: The findings highlight that high prepregnancy BMI and exceed GWG contributed to increased risk of preeclampsia with a superimposed effect and underscore the need to optimize the recommendations for GWG for women with different prepregnancy BMI.